Prediction of perioperative complications and mortality in patients with complicated forms of colon cancer - Kubrak, M. A.; Zavhorodnii, S. M.; Danyliuk, M. B. (Zaporozhye Medical Journal, 2024)
Complicated forms of colon cancer occupy a significant share of emergency operations in general surgical departments with high rates of mortality and complications. Assessment of possible complications and mortality before surgery is an important aspect in choosing treatment tactics for this group of patients. The aim of the study. To analyze the risks of complications and mortality in the perioperative period in patients with complicated forms of colorectal cancer using the prognostic CR-POSSUM scoring system and to determine the critical levels of the CR-POSSUM score using ROC analysis. Materials and methods. The data of 71 (100 %) patients who were treated for complicated forms of colorectal cancer were analyzed. The studied group included 36 (50.71 %) men and 35 (49.29 %) women aged 67.97 ± 12.71 years. In the postoperative period, complications were found in 32 (45.07 %) patients, there were 8 (11.27 %) deaths. Results. The mortality risk at the time of hospitalization was 6.40 (3.50; 19.10) %. The actual mortality rate in the studied group was 8 (11.27 %) patients, which corresponded to the CR-POSSUM theoretically calculated mortality risk, U = 234.0, p = 0.739. Conclusions. Increased level of complications was noted at the critical score ˃20 points, AUC = 0.744, p ˂ 0.001 (sensitivity – 71.0 %, specificity – 67.5 %) and the critical score of increasing the mortality rate was ˃22 points, AUC = 0.781, p = 0.005 (sensitivity – 75.0 %, specificity – 74.6 %) as defined by CR-POSSUM. According to the ROC analysis, the increase in mortality in the studied group did not depend on the character and complexity of surgical interventions (p = 0.159), but on the general patient condition at the time of hospital admission (р ˂ 0.001). At the same time, the increased level of complications in the group depended on both the character and complexity of the surgical intervention (p = 0.028) and on the general patient health at the time of hospitalization to the general surgical department (р ˂ 0.001).